Pomelo Green Production on Acidic Soil: Reduce Traditional Fertilizers, but Do Not Ignore Magnesium - Chen, Xiaohui; Yan, Xiaojun; Muneer, Muhammad Atif; Weng, Xuefan; Cai, Yuanyang; Ma, Changcheng; Liu, You; Zhang, Siwen; Zhang, Weiqiang; Yang, Wenhao; Wu, Liangquan; Zhou, Shungui; et al. (Frontiers in Sustainable Food Systems, 2022)
Orchards in acid soils are at risk of magnesium (Mg) deficiency which negatively affects the plant growth, yield, and quality. However, the impacts of Mg supplementation on fruit yield, quality, and environmental and economic benefits have only been rarely addressed. We conducted 15 pomelo (Citrus grandis L.) orchard trials in South China to assess more efficient integrated nutrient management (INM) practices, including local farmer fertilization practices (FP; average application rate of nitrogen, phosphorus, and potassium were 1,075 kg N ha−1, 826 kg P2O5 ha−1, and 948 kg K2O ha−1, respectively), optimum fertilization practice (OPT; average application rate of nitrogen, phosphorus, and potassium were 550 kg N ha−1, 295 kg P2O5 ha−1, and 498 kg K2O ha−1, respectively) and optimum fertilization supplemented with Mg (OPT+Mg; average application rate of Mg was 196 kg MgO ha−1). The results showed that the yield, total soluble solid-to-titratable acidity ratio, and economic benefits under OPT practice were not significantly different from those of FP, while those of OPT+Mg were significantly higher than those of FP, by 8.76, 8.79, and 15.00%, respectively, while titratable acidity contents were significantly lower by 7.35%. In addition, compared with those from FP, the energy inputs and greenhouse gas (GHG) emissions from OPT were 31.00 and 26.48% lower, and those from OPT+Mg were 26.71 and 23.40% lower, respectively. Compared with those of OPT, the marginal efficiency of energy, GHG emissions, and capital of Mg under OPT+Mg were reduced by 62.30, 44.19, and 21.07%, respectively. Overall, adopting OPT+Mg for pomelo production could further enhance yield, fruit quality, and economic benefits while reducing the environmental burdens.